The Implications of Online Gambling on Family Integrity: An Islamic Law Perspective : A Case Study of the Community in Palu City, Indonesia - Mohammad Fauzan; Nasaruddin Nasaruddin; Kamaruddin Kamaruddin (State Islamic University Datokarama Palu, 2026)
The rapid development of information and communication technology has provided various benefits to society; however, it has also contributed to emerging social problems, including the increasing prevalence of online gambling. This phenomenon affects not only individuals’ economic and psychological well-being but also family integrity and harmony. This study aims to analyse the implications of online gambling for family integrity in Palu City and to examine the phenomenon from the perspective of Islamic law. This research employs a qualitative empirical approach. Data were collected through observation, interviews, and documentation involving families affected by online gambling in Palu City. The data were analysed descriptively and interpretively using phenomenological and structural-functional approaches and were further examined through the framework of maqāṣid al-sharīʿah. The findings reveal that the primary motives for engaging in online gambling include curiosity, the desire for financial gain, entertainment, and addiction. The practice generates significant negative impacts on economic, psychological, social, and spiritual aspects of family life. From the perspective of Islamic law, online gambling is prohibited (haram) because it constitutes maisir and contradicts the objectives of Islamic law, particularly the protection of wealth, life, intellect, and progeny. Consequently, online gambling poses a serious threat to the resilience and integrity of Muslim families.